Media spy ([Australia] : Media Spy, 2007)
"Media Spy is Australia's leading site dedicated to covering the media industry, with an emphasis on news and current affairs coverage, issues within Australian television today, as well as the shows we watch and how they rate. Over the years, Media Spy has been a favourite of industry insiders, who've offered their insight and analysis on what's happening behind the scenes. Media Spy is proud to maintain a diverse mix in our membership, with people from across the country and around the world logging on to take part in discussions on a range of topics."
Title from title screen (viewed on 9 July 2009)
Text and graphics
Mode of access: Internet via World Wide Web. Available at: http://www.mediaspy.org
Selected for archiving
Keywords: Radio broadcasting -- Australia; Television broadcasting -- Australia